Mapping the Melatonin Receptor. 8. Selective MT2 Agonists Derived from 5, 6‐Dihydroindolo[2, 1‐a]isoquinolines and Related Systems. (9th May 2022) - Tsotinis, Andrew; Afroudakis, Pandelis A.; Papanastasiou, Ioannis P.; Sakellaropoulou, Aikaterini; Boniakou, Marina; Komiotis, Dimitri; Garratt, Peter J.; Delagrange, Philippe; Bocianowska‐Zbrog, Alina; Sugden, David
Abstract: A series of substituted indolo[2, 1‐ a ]isoquinolines and indolo[1, 2‐ a ]benzoxazines have been prepared, as melatonin analogues, to investigate the nature of the binding site of the melatonin receptor. Agonist and antagonist potency of all the analogues was measured using the [35S]GTPγS binding assay protocol. The binding affinity of the analogues were measured by competition binding studies against the human MT1 (hMT1) and MT2 (hMT2) receptors stably transfected in Chinese Hamster Ovarian (CHO) cells, using 2‐[ 125 I]‐iodomelatonin, as a ligand. N ‐Acetyl 2‐(10‐methoxy‐5, 6‐dihydroindolo[2, 1‐ a ]isoquinolin‐12‐yl)propyl‐1‐amine (12 a) binds strongly to both the hMT1 and hMT2 receptors, and shows a preference for the hMT2, as does its propanamido counterpart 12 b . The introduction of two methyl groups into their side chain, analogues 15 a and 15 b, leads to antagonism, in the case of the former, and drastically diminishes its hMT1 binding; an analogous profile is seen for 15 b, which, however, is a partial agonist. Introduction of chlorine or methoxy groups into ring 4 gives compounds, that are weakly binding, with a preference for MT2. Substitution of oxygen for carbon at position 5 gives the indolo[1, 2‐ c ]benzoxazines 33, 36 a and b, that bind strongly to the human receptors, 33, 36 b being potent agonists at the melatonin receptors, but do not discriminate between hMT1 and hMT2. Abstract : Subtle differences : Aiming at the preparation of ligands selective for melatonin receptors, herein we present the synthesis and biology of new 5, 6‐dihydroindolo[2, 1‐ a ]isoquinoline and indolo[1, 2‐ a ]benzoxazine tetracyclic analogues. The results nicely illustrate the subtle differences between the two melatonin receptors, mainly with incremental changes in the side chains of the new ligands.